Expanding the Phenotypic Spectrum of GPI Anchoring Deficiency Due to Biallelic Variants in GPAA1. (21st December 2021) - Castle, Alison M.R.; Salian, Smrithi; Bassan, Haim; Sofrin-Drucker, Efrat; Cusmai, Raffaella; Herman, Kristin C.; Heron, Delphine; Keren, Boris; Johnstone, Devon L.; Mears, Wendy; Morlot, Susanne; Nguyen, Thi Tuyet Mai; et al.
Abstract : Background and Objectives: To expand the clinical knowledge of GPAA 1-related glycosylphosphatidylinositol (GPI) deficiency. Methods: An international case series of 7 patients with biallelic GPAA1 variants were identified. Clinical, biochemical, and neuroimaging data were collected for comparison. Where possible, GPI-anchored proteins were assessed using flow cytometry. Results: Ten novel variants were identified in 7 patients. Flow cytometry samples of 3 available patients confirmed deficiency of several GPI-anchored proteins on leukocytes. Extensive phenotypic information was available for each patient. The majority experienced developmental delay, seizures, and hypotonia. Neuroimaging revealed cerebellar anomalies in the majority of the patients. Alkaline phosphatase was within the normal range in 5 individuals and low in 1 individual, as has been noted in other transamidase defects. We notably describe individuals either less affected or older than the ones published previously. Discussion: Clinical features of the cases reported broaden the spectrum of the known phenotype of GPAA1 -related GPI deficiency, while outlining the importance of using functional studies such as flow cytometry to aid in variant classification.